Az utolsó beszélgetés Aczél Györggyel, nem sokkal a halála előtt 1991-ben - Szinetár, Miklós (Hungary : ATV, 2017)
The dominant cultural politician of the Kádár regime tells about the last decade of the regime, about the turn in 1985, when the reform policy in Hungary came to a halt and Aczél himself was pushed out of decision-making.
Keywords: Documentary films